COVID−19, Anti-NMDA Receptor Encephalitis and MicroRNA - Wang, Hsiuying (Frontiers in Immunology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has had an enormous impact on the world, affecting people’s lifestyle, economy, and livelihood. Recently, with the development of vaccines, the number of infected cases has decreased. Many case reports have revealed that COVID-19 may induce other serious comorbidities such as anti-N-methyl-d-aspartate (anti-NMDA) receptor encephalitis. Anti-NMDA receptor encephalitis is an acute autoimmune disease that occurs more commonly in women than in men. To explore the association between COVID-19 and anti-NMDA receptor encephalitis, the microRNA (miRNA) biomarkers of COVID-19, anti-NMDA receptor encephalitis, and other related diseases from the literature are reviewed; then on the basis of these miRNA biomarkers, the relationship between COVID-19 and anti-NMDA receptor encephalitis is discussed. miRNAs are small non-coding RNAs that play important roles in cell differentiation, development, cell-cycle regulation, and apoptosis. miRNAs have been used as biological biomarkers for many diseases. The results in this study reveal that the relationship between anti-NMDA receptor encephalitis and COVID-19 infection or COVID-19 vaccination cannot be excluded; however, the risk that COVID-19 triggers the anti-NMDA receptor encephalitis is not high.